Axis inhibition protein 1 (Axin1) Deletion–Induced Hepatocarcinogenesis Requires Intact β-Catenin but Not Notch Cascade in Mice - Qiao, Yu (Hepatology, 2019)
Inactivating mutations of axis inhibition protein 1 (AXIN1), a negative regulator of the Wnt/β-Catenin cascade, are among the common genetic events in human hepatocellular carcinoma (HCC), affecting approximately 10% of cases. In the present manuscript, we sought to define the genetic crosstalk between Axin1 mutants and Wnt/β-catenin as well as Notch signaling cascades along hepatocarcinogenesis. We discovered that c-MET activation and AXIN1 mutations occur concomitantly in ~3%–5% of human HCC samples. Subsequently, we generated a murine HCC model by means of CRISPR/Cas9-based gene deletion of Axin1 (sgAxin1) in combination with transposon-based expression of c-Met in the ouse liver (c-Met/sgAxin1). Global gene expression analysis of mouse normal liver, HCCs induced by c-Met/sgAxin1, and HCCs induced by c-Met/ΔN90-β-Catenin revealed activation of the Wnt/β-Catenin and Notch signaling in c-Met/sgAxin1 HCCs. However, only a few of the canonical Wnt/β-Catenin target genes were induced in c-Met/sgAxin1 HCC when compared with corresponding lesions from c-Met/ΔN90-β-Catenin mice. To study whether endogenous β-Catenin is required for c-Met/sgAxin1-driven HCC development, we expressed c-Met/sgAxin1 in liver-specific Ctnnb1 null mice, which completely prevented HCC development. Consistently, in AXIN1 mutant or null human HCC cell lines, silencing of β-Catenin strongly inhibited cell prolif-eration. In striking contrast, blocking the Notch cascade through expression of either the dominant negative form of the recombinant signal-binding protein for immunoglobulin kappa J region (RBP-J) or the ablation of Notch2 did not significantly affect c-Met/sgAxin1-driven hepatocarcinogenesis. Conclusion: We demonstrated here that loss of Axin1 cooperates with c-Met to induce HCC in mice, in a β-Catenin signaling–dependent but Notch cascade–independent way.